Orchard grass safeguards sustainable development of fruit industry in China. (1st January 2023) - Ren, Jing; Li, Fuduo; Yin, Changbin
Abstract: Orchard grass has received extensive attention in recent years due to its environmental-friendly features, yet the comprehensive effects of yield, quality, environment and economics in grass-planted orchard in the long term don't still remain fully understood. The study quantified the yield, quality, environmental and economic effects of orchard grass, aiming to provide a reference for the application of grass for fruit production in China. Meta-analysis results firstly illustrate that the application of orchard grass has positive effects on fruit yield increase and quality improvement. The underlying drivers of these positive changes in fruit yield and quality are enhancements of soil properties in orchard. Secondly, long-term planting of orchard grass positively impacts soil properties linked to healthy soil and warrants fruit production. Finally, cost-benefit analysis reveal that the economic benefits of planting grass in orchards are 1.36%–2.08% higher than that of clear tillage control. Therefore, orchard grass is a sustainable safeguard to promote the development of fruit industry in the long run. Many corresponding measures should be taken to rapidly promote green manure areas and limit further increase of chemical fertilizer to maintain the sustainability of orchards. Highlights: Meta–analysis was used to reveal comprehensive effects of grass orchard. The economic benefits of grass orchard and conventional orchard were compared. Orchard grass can improve fruit yield and quality by raising soil fertility etc. The responses to yield and quality under orchard grass varied with external factors.